The potential of transcranial magnetic stimulation for population-based application: a region-based illustrated brief overview. (2nd October 2014) - Mahayana, Indra T.; Sari, Dwi C. R.; Chen, Chiao-Yun; Juan, Chi-Hung; Muggleton, Neil G.
<x xml:space="preserve">Abstract</x> The awareness of the global trends in neuroscience study, especially in the cognitive neuroscience field, should be increased. One notable approach is the use of transcranial magnetic stimulation (TMS) not only as a research tool but also as a choice for treatment and rehabilitation in neurological disorders, such as post-stroke hemiplegia, visuospatial neglect syndrome, Alzheimer's disease (AD) and psychiatric conditions such as major depression and schizophrenia. All of these occur in significant numbers in highly populated regions. This paper briefly discusses the basic protocols and potential benefits of using TMS with the aim of providing insight that is useful in the design of future public health strategies in highly populated regions with a large neurocognitive burden of disease where this technique is currently underemployed.